Een Scheurkalender : 1996. (Roeselare : Fotogravure Deckmyn, 1996)
Debaene, Mario ; Hespeel, Jan ; Boodts, Dion ; Vandewalle, Luc ; Vandenabeele, Isabelle ; Van Lancker, Pol ; Lamiroy, Mieke ; Hardt, Bruno ; Michiels, Steve ; Goovaerts, Tom ; Schoofs, Bart ; Swenne, Olivier ; van der Gucht, Virginie ; Ysenbaert, Filip ; Vandewalle, Luc ; Smeets, Irama ; Van Hasten, Steven ; Vaes, Wim ; Vandenbussche, Bjorn ; Marboeuf, Olivier ; Lens, Jan ; Van Lancker, Pol ; Frateur, Jeroen ; Clarisse, Geert ; Vandenbussche, Bjorn ; Michiels, Steve ; Schamp, Tom ; Lamiroy, Mieke ; Vermeulen, Sander ; Creten, Peter ; Van Goethem, Anaïs ; Goblet, Dominique ; Ducatteeuw, Joost Felix ; Lambé, Eric ; vantieghem, Bart ; Fortemps, Vincent ; Lezy, Bert ; Gobbaerts, Bertrand ; Verscheure, Geert ; Degryse, Luc ; Verstraete, David ; Deprez, Denis ; Long, Jean-Christophe ; Alagbé, Yvan ; Way, Pang Ting ; Van Hasselt, Thierry
Nederlands
boek